Licht-Räume. - Museum Folkwang Essen; Bauhaus, Dessau (Essen : Museum Folkwang, 1993)
Adams, Dennis ; Albrecht, Jürgen ; Barrette, Bill ; Bohnenberger, Stefan ; Dohr, Günter ; Geleynse, Wyn ; Goulbier, Yvonne ; Katase, Kazuo ; Kuball, Mischa ; Laugs, Martha ; Mattner, Jakob ; Nauman, Bruce ; Raynaud, Patrick ; Rogl, Alexander ; Wagner K, Matthias
Licht-Räume, Museum Folkwang Essen, 1993 / Bauhaus, Dessau, 1994
boek